Romanian Inventory of Depression and Anxiety Symptoms (IDAS-II) - Petre, Ligiana Mihaela; Gheorghe, Delia Alexandra; Watson, David; Mitrofan, Laurentiu (Frontiers in Psychology, 2023)
Background: The Inventory of Depression and Anxiety Symptoms (IDAS-II) is a self-report measure comprising 99 items divided into 18 non-overlapping scales that allows for a dimensional assessment of depression, anxiety, and bipolar symptoms. The IDAS-II is currently available in English, Turkish, Spanish, German, and Swedish. This study's major goal was to adapt and validate the IDAS-II to the Romanian population. Method: Participants from a community sample (N = 1072) completed the IDAS-II (Romanian version) and additional measures assessing depression and anxiety disorders. Results: Item-level factor analyses validated the unidimensionality of the scales, and internal consistency results indicated that most symptom scales had satisfactory alpha coefficient values. Based on exploratory results by Watson et al. (2012), a confirmatory factor analysis (CFA) on the IDAS-II scales confirmed a three-component model of "Distress," "Obsessions/Fear," and "Positive Mood." Convergent and discriminant validity were established by correlational analyses with other symptom measures. Limitations: This study was conducted using a sample from the general population and several of the employed measures have limitations. Specifically, the current study was unable to employ Romanian versions of the gold-standard instruments that assess well-being, obsessive-compulsive disorder, and claustrophobia. Conclusion: The IDAS-II (Romanian version) is the first clinical measure to assess internalizing dimensions of the Hierarchical Taxonomy of Psychopathology (HiTOP) model that is available for the Romanian population.